The Pocket-Creation Method Facilitates Endoscopic Submucosal Dissection of Gastric Neoplasms Along the Lesser Curvature at the Gastric Angle - Kitamura, Masafumi; Miura, Yoshimasa; Shinozaki, Satoshi; Lefor, Alan Kawarai; Yamamoto, Hironori (Frontiers in Medicine, 2022)
Background Endoscopic submucosal dissection (ESD) of superficial gastric lesions located along the lesser curvature at the gastric angle is a challenging situation due to paradoxical movement and a protruding angle. The pocket-creation method (PCM) can overcome this difficulty by stabilizing the tip of the endoscope in the pocket and minimizing insufflation of the stomach, which enables horizontal and straight dissection. This study aims to clarify whether the PCM improves the technical outcomes of ESD of superficial gastric neoplasms along the lesser curvature at the angle. Methods From October 2006 to June 2021, 158 gastric lesions along the lesser curvature at the angle were resected with needle-type knives. We retrospectively reviewed the records and divided them into the PCM group (n = 61) and the conventional method (CM) group (n = 97). The primary outcome measurement was dissection speed (in mm2/min). Results The two groups were not significantly different for baseline characteristics such as macroscopic type and size except for the proportion of adenomas. The proportion of expert endoscopists was not significantly different between the two groups (P = 0.141). The dissection speed was significantly faster in the PCM group than in the CM group (P = 0.001). There were no holes in the resected specimens in the PCM group, while five lesions in the CM group (5%) had a hole (P = 0.182). There were no significant differences in the incidence of adverse events. Conclusions This is the first study to show that the PCM outperforms the CM for ESD of lesions located along the lesser curvature at the gastric angle. The PCM facilitated ESD of these lesions by significantly increasing dissection speed when a needle-type knife is used with no increase in adverse events.